2008
DOI: 10.1124/dmd.108.022764
|View full text |Cite
|
Sign up to set email alerts
|

Lacteal Secretion, Fetal and Maternal Tissue Distribution of Dasatinib in Rats

Abstract: gland, mammary tissue, lungs, kidneys, liver, and placenta. Compared with maternal tissues, a relatively low level of radioactivity was detected in fetal tissues. The concentrations of dasatinibequivalents in fetal liver and kidneys were <13% of the respective maternal organs. The C max of dasatinib-equivalents in fetal blood was approximately 39% of that in maternal blood; however, the AUC values were comparable. Fetal brain/blood ratios of C max and AUC 0-inf were approximately 1.58 and 1.48, respectively, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
29
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(32 citation statements)
references
References 26 publications
3
29
0
Order By: Relevance
“…In rats, dasatinib was observed to be teratogenic, extensively distributed in maternal tissues, and secreted into milk [17].…”
Section: Dasatinibmentioning
confidence: 99%
“…In rats, dasatinib was observed to be teratogenic, extensively distributed in maternal tissues, and secreted into milk [17].…”
Section: Dasatinibmentioning
confidence: 99%
“…Embryo-foetal defects seen included skeletal malformations at multiple sites (scapula, humerus, femur, radius, ribs and clavicle), reduced ossification (sternum, vertebrae, pelvis and hyoid body), oedema and microhepatia [4]. It is not known whether dasatinib is secreted in human milk, but from animal studies, dasatinib was found to be excreted into milk in female rats [6].…”
Section: Dasatinibmentioning
confidence: 99%
“…75 Dasatinib, a dual BCR-ABL/src kinase inhibitor crosses the placenta and leads to considerable levels in fetal plasma. 81 In the first trimester, dasatinib has been reported to cause fetal hydrops and severe fetal bicytopenia, 76 but normal pregnancies have also been reported. 74,[77][78][79] HC is a cytotoxic agent that inhibits RNA synthesis and is commonly used for cytoreduction in newly diagnosed CML, prior to therapy with TKI.…”
Section: Chronic Leukemias Chronic Myeloid Leukemiamentioning
confidence: 99%